Solvent-based emulsion, preparation method and application thereof, and adhesive
By using a solvent-based emulsion with a modified hydrogenated styrene elastomer to form a cross-linked interpenetrating network structure with polyester resin, the problems of insufficient flexibility and dielectric properties of FFC adhesives are solved, and a high-performance adhesive suitable for various electronic products is prepared.
Patent Information
- Application Number
- CN202511847047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-01-23
AI Technical Summary
Existing FFC adhesives have shortcomings in terms of flexibility, dielectric properties and processability. They are difficult to achieve a balance between high flexibility, low dielectric constant and dielectric loss tangent, and the processing is complex and costly.
A solvent-based emulsion with a cross-linked interpenetrating network structure formed by modified hydrogenated styrene elastomer and polyester resin was prepared by controlling the degree of phase separation to form an O/O type emulsion. Combined with hollow microspheres and flame-retardant fillers, a uniform and stable adhesive was formed.
This adhesive achieves high flexibility, low dielectric constant, and positive dielectric loss tangent, with strong adhesion and easy processing. It is suitable for FFC, printed circuit boards, touch screens, electronic devices, semiconductor products, and packaging.
Smart Images

Figure CN121379472A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of adhesives, in particular to a solvent type emulsion, a preparation method and application thereof, and an adhesive. BACKGROUND
[0002] Flexible Flat Cable (FFC) is a kind of high-density, extremely flexible interconnection assembly made of extremely thin flat copper wire conductors, which is laminated between insulating film materials by automatic equipment. FFC has become an indispensable basic element in electronic products due to its ultra-thin thickness, excellent bending performance and flexible customizability. With the application trend of device miniaturization, high integration and high-speed high-frequency signal, higher and higher requirements are put forward for the bending property, processing precision and dielectric performance of FFC.
[0003] At present, the adhesive film in the middle of FFC is mainly epoxy or polyester thermosetting adhesive film and polyolefin thermoplastic adhesive film. The polyester or epoxy thermosetting adhesive film has good processability and strong adhesion to copper wire and base film, but has insufficient dielectric performance and flexibility. The polyolefin thermoplastic adhesive film has good flexibility and dielectric performance, but has poor processability and adhesion. There are also two materials used in blending, but the compatibility is poor and the processing difficulty is large.
[0004] CN109628015A provides a polyolefin hot melt adhesive and a method for making the same, and a composite insulating material using the same. By adding polystyrene hollow microspheres to the polyolefin hot melt adhesive, the adhesive film has low polarity, low hygroscopicity, strong insulation performance and stable voltage resistance performance. However, the hot melt adhesive film is only suitable for use as a single insulating layer, has poor adhesion, and has general high temperature resistance.
[0005] CN102382382B provides a thermoplastic resin composition with excellent adhesion to base film and conductor wiring, and low relative dielectric constant and dielectric loss tangent. By combining a polyphenylene ether polymer with hydroxyl groups and a hydrogenated styrene elastomer, low dielectric constant and low dielectric loss tangent are achieved, and excellent adhesion to the conductor wire is achieved. However, the combination has general bending resistance, and the overall polarity of the adhesive layer is low, and the adhesion to the base film needs to be enhanced by a pre-coating layer.
[0006] CN110121533B provides a polyester resin composition, which has excellent adhesion to polyester film and metal, and can be used as an adhesive for FFC used in internal wiring of electronic devices. By designing a crystalline polyester resin with low Tg and high Tm, the heat resistance and salt water resistance of the adhesive layer are improved.
[0007] CN116554824A provides an adhesive, rapid hot pressing film and flexible flat cable, through the combination of polyester resin, phenolic epoxy resin and toughening resin, realizing high bonding strength and high weather resistance, but the dielectric performance and flexibility of the adhesive layer are poor.
[0008] TW201339268A provides a preparation method of a styrene block copolymer with high melt flow rate, low viscosity, high strength and good elastic properties, and through graft modification, it can realize mutual solubility with epoxy resin, acrylic, styrene, vinyl ester or polyester resin, etc.
[0009] In summary of the above patents, the combination of polyester and polyolefin in FFC adhesive is often mixed by melt co-extrusion or direct mixing and dissolution by modifying polyolefin, which cannot break through the upper limit of the performance of a single material and cannot exceed the performance of two materials; and chemical modification often limits the molecular structure design, resulting in complex processing technology or cost explosion.
[0010] Therefore, there is an urgent need in the art to develop an adhesive with high flexibility, low dielectric constant and dielectric loss tangent, which is simple to process, low in cost and good in adhesion to the substrate and wire.
[0011] In view of this, the present application is proposed. SUMMARY
[0012] The purpose of the present application is to provide a solvent type emulsion and its preparation method and application, and an adhesive, to solve or improve the above technical problems.
[0013] The present application is implemented as follows: In a first aspect, the present application provides a solvent type emulsion, the solid content of the solvent type emulsion being 35%-45%; The components include, by mass fraction, 20-40 parts of modified hydrogenated styrene elastomer, 60-80 parts of mixed solvent and 48-55 parts of polyester resin liquid.
[0014] In a second aspect, the present application provides a preparation method of the solvent type emulsion according to any one of the preceding embodiments, comprising the following steps: The modified hydrogenated styrene elastomer and the mixed solvent are mixed uniformly at a temperature of 85-95 DEG C, and then cooled to 50-60 DEG C to prepare a first system; The polyester resin liquid is added to the first system to prepare the solvent type emulsion.
[0015] In a third aspect, the present application provides an adhesive, comprising the solvent type emulsion according to any one of the preceding embodiments or prepared by the preparation method according to any one of the preceding embodiments; The adhesive comprises the following components by mass fraction: 100-150 parts of the solvent-based emulsion, 5-15 parts of the hollow microspheres, 20-40 parts of the flame-retardant filler, 10-30 parts of the curing agent, and 20-100 parts of the solvent.
[0016] In a fourth aspect, the embodiments of the present application provide an application of the adhesive according to any one of the preceding embodiments in the preparation of a flexible flat cable, which comprises the following steps: The adhesive is prepared by mixing the solvent-based emulsion, the hollow microspheres, the flame-retardant filler, the curing agent, and the solvent in proportion; After the adhesive is coated on the base film, the intermediate is prepared by drying treatment at a temperature of 80-100 DEG C for 20-40 s, and the dry film thickness is 40-60 mu m; The intermediate is laminated with the conductor, and then the flexible flat cable is prepared by aging treatment at a temperature of 60-100 DEG C for 1-3 days.
[0017] In a fifth aspect, the embodiments of the present application provide an application of the adhesive according to any one of the preceding embodiments in the fields of printed circuit boards, touch screens, electronic devices, and semiconductor products and packaging.
[0018] The present application has the following beneficial effects: The solvent-based emulsion provided by the embodiments of the present application is prepared by emulsifying the modified hydrogenated styrene elastomer with a suitable polyester resin, and the O / O type solvent-based emulsion is prepared by controlling the cross-linking and curing conditions, so that the phase separation degree of the hydrogenated styrene elastomer and the polyester can be controlled to achieve a cross-linking interpenetrating network structure. The prepared adhesive has the characteristics of uniform stability, convenient sizing, strong adhesion, good adhesion to the base film and the conductor, and simple processing. The adhesive layer formed by the adhesive has the characteristics of lower dielectric constant and dielectric loss tangent and higher elastic modulus, so that the final material structure is more stable and has better heat resistance, and is expected to be widely applied. BRIEF DESCRIPTION OF DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the present application, and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can also be obtained without creative labor.
[0020] Figure 1 The emulsion is in a uniform stable state of milky white; Figure 2 The emulsion is in a phase separation state; Figure 3 The solution is in a clear and transparent state. DETAILED DESCRIPTION
[0021] In order to make the purposes, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below. If specific conditions are not indicated in the embodiments, conventional conditions or conditions suggested by manufacturers are adopted. If manufacturers of reagents or instruments are not indicated, all are conventional products that can be purchased in the market.
[0022] The present application aims to provide a solvent type emulsion and a preparation method and application thereof, so as to solve or improve the above technical problems.
[0023] The present application is implemented as follows: In a first aspect, the present application provides a solvent type emulsion, and the solid content of the solvent type emulsion is 35%-45%. The modified hydrogenated styrene elastomer and the polyester resin solution provided by the present application form a cross-linked interpenetrating network structure in the curing process, which is beneficial to improve the modulus and strength of the adhesive layer, enhances the toughness, makes the material structure more stable, and has better heat resistance, and the specific analysis is as follows: By selecting a suitable hydrogenated styrene elastomer, modifying it, and preparing an O / O type emulsion, the emulsion realizes controllable micro-phase separation with the polyester resin in the curing process of the adhesive layer, so as to form a cross-linked interpenetrating network structure. The conventional method for polyolefin is melt blending and mixing after modification to realize miscibility. The melt blending method cannot be cross-linked and cured with isocyanate, and the miscibility after modification cannot realize the cross-linked interpenetrating structure. In the present application, the hydrogenated styrene elastomer is emulsified as a dispersed phase, which is wrapped by the polyester solution, so that the controllable micro-phase separation can be better realized, compared with ordinary blending or modified miscibility, the modulus and strength of the adhesive layer are improved, the toughness is enhanced, the material structure is more stable, and the heat resistance is better.
[0024] In an optional embodiment, the modified hydrogenated styrene elastomer includes the following components in mass fraction: 80-100 parts of hydrogenated styrene elastomer, 14-22 parts of white oil, 0.08-0.12 parts of p-di-tert-butyl peroxide isopropyl benzene, and 1.5-2 parts of grafting monomer; and the grafting rate of the modified hydrogenated styrene elastomer is 0.8%-1.2%.
[0025] Further, the modified hydrogenated styrene elastomer includes the following components in mass fraction: 100 parts of hydrogenated styrene elastomer, 20 parts of white oil, 0.1 parts of p-di-tert-butyl peroxide isopropyl benzene, and 2 parts of grafting monomer.
[0026] Further, the modified hydrogenated styrene elastomer includes the following components in mass fraction: 100 parts of hydrogenated styrene elastomer, 20 parts of white oil, 0.1 parts of p-di-tert-butyl peroxide isopropyl benzene, and 2 parts of grafting monomer.
[0027] The hydrogenated styrene elastomer is selected from at least one of SEBS, SIBS and SEPS; the grafting monomer comprises at least one of the following groups: epoxy group, acid anhydride group.
[0028] Optionally, the SEBS and SEPS have the following characteristics respectively: number average molecular weight of 50000-150000, styrene content of 30%-40%, elongation of 500%-800%; the SIBS has the following characteristics: number average molecular weight of 80000-150000, styrene content of 15%-25%, elongation of ≥800%.
[0029] Exemplarily, the SEBS in the embodiment of the application can be selected from at least one of Li Changrong 8510U, Li Changrong 9552, Li Changrong 9557D and KRATON G1650; the SEPS can be selected from at least one of Li Changrong 8501U and Li Changrong 8600U; the SIBS can be KRATON D1171; in other embodiments of the application, or according to actual needs, other brands and specifications of hydrogenated styrene elastomers can be selected.
[0030] Optionally, the preparation of the modified hydrogenated styrene elastomer comprises the following steps: The hydrogenated styrene elastomer, white oil, p-di-tert-butyl peroxyisopropylbenzene and grafting monomer are mixed uniformly in proportion, and then extruded, cut, extracted, separated and dried under the condition of a twin-screw extruder and a temperature of 160-180°C to obtain the modified hydrogenated styrene elastomer.
[0031] The parameters of the twin-screw extruder are as follows: screw diameter 35mm, L / D=0.36, screw rotation speed 150-300rpm, temperature setting: feeding zone 140-160°C, melting mixing zone 160-180°C, reaction zone 160-180°C, homogenization / exhaust zone 170-180°C, die head 160-170°C.
[0032] In the embodiment of the application, the temperature and time of each stage can be reasonably adjusted according to the actual amount and ratio of the material.
[0033] Optionally, the grafting monomer is selected from at least one of Maleic Anhydride (MAH), Glycidyl Acrylate (GA), Allyl Glycidyl Ether (AGE), Glycidyl Methacrylate (GMA) and Itaconic Anhydride (IAH or ITA).
[0034] In an optional embodiment, the mixed solvent comprises butanone and other reagents in a volume ratio of 1:(0.8-1.3), and the other reagents are selected from at least one of butyl acetate, propyl acetate, methyl isobutyl ketone, and dimethyl carbonate.
[0035] Exemplarily, the volume ratio of butanone and other reagents in the mixed solvent can be selected from any one of 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, and 1:1.3, or other values within the range of 1:(0.8-1.3).
[0036] And / or, the solvent of the polyester resin solution comprises butanone, and the solid content is 58%-65%.
[0037] The solid content of the polyester resin solution refers to that, in 100 g of the polyester resin solution, 58%-65% of polyester resin is contained, and the rest is solvent. The setting of the solid content has a direct impact on the final solid content of the solvent-based emulsion, and can be reasonably adjusted according to actual needs. In order to enhance the mutual solubility, the solvent of the polyester resin solution is butanone, which is the same as the mixed solvent.
[0038] If the solid content is higher, the viscosity of the resin solution is higher, and too high viscosity will cause stirring difficulty in the later stage of reaction, poor heat transfer, and even discharge difficulty, which may affect the storage stability and increase the risk of gelation. If a product with low solid content is needed, it will be diluted excessively, increasing the packaging and transportation costs.
[0039] Exemplarily, the solid content of the polyester resin solution can be selected from any one of 58%, 59%, 60%, 61%, 62%, 63%, and 65%, or other values within the range of 58%-65%.
[0040] Optionally, the polyester resin has a Tg of-30℃ to 14℃, a number average molecular weight of 10000-40000, a hydroxyl value of 3 mgKOH / g-10 mg KOH / g, and an acid value of 0 mg KOH / g-5 mg KOH / g.
[0041] Optionally, the polyester resin is selected from at least one of AL061M and AL177.
[0042] Further, AL061M has a Tg of-6℃, a number average molecular weight of 21442, a hydroxyl value of 4.1 mg KOH / g, and an acid value of 0.3 mg KOH / g; and AL177 has a Tg of 15℃, a number average molecular weight of 25414, a hydroxyl value of 4.2 mg KOH / g, and an acid value of 0.9 mg KOH / g. In other embodiments of the present application, the specific type of polyester resin and the specific specifications of AL061M and AL177 can be reasonably selected according to actual needs.
[0043] In a second aspect, the present application provides a method for preparing the solvent-based emulsion according to any one of the preceding embodiments, comprising the following steps: The modified hydrogenated styrene elastomer and the mixed solvent are mixed uniformly at a temperature of 85-95°C, and then cooled to 50-60°C to obtain a first system; The polyester resin solution is added to the first system to obtain the solvent-based emulsion.
[0044] It should be noted that the hydrogenated styrene elastomer is modified by grafting a polar group, which induces self-emulsification of the modified hydrogenated styrene elastomer in the solvent, and the continuous phase is a polyester solution, so that the final solvent-based emulsion is an O / O emulsion structure as a whole.
[0045] In an optional embodiment, the temperature of the reaction system is reduced to 50-60°C at a rate of 2-3°C / 5 min; it should be noted that the emulsion is essentially a thermodynamically unstable system, and when the temperature is suddenly reduced, the density, viscosity and interfacial tension between them will change dramatically and unsynchronized. Controlling the cooling rate allows the emulsion system to have enough time to adapt and smoothly transition to a new thermodynamic state, thereby maximizing its uniformity and stability, and the product performance is controllable and reproducible.
[0046] The device for preparing the first system is an emulsification kettle, and in other embodiments of the present application, the device can be reasonably selected according to actual conditions; in order to ensure the efficient preparation of the first system and the uniformity of the system, stirring can be performed during the preparation process, and the stirring rate is reasonably adjusted according to actual conditions, such as 300 rpm, 400 rpm, 500 rpm, etc.
[0047] And / or, the polyester resin solution is added to the first system at a rate of 1.5-2.5 parts / min; when the polyester resin is poured into the first system too quickly, it cannot be quickly dispersed and mixed, and a high-concentration "lump" of polyester resin is formed near the addition point. The inside of the lump is difficult to be effectively infiltrated and dispersed by the elastomer, leading to macroscopic phase separation, and even after subsequent stirring, micro-rich resin regions may remain, destroying the continuity and uniformity of the system.
[0048] In order to ensure the uniformity, stability and compatibility of the system, the rotation speed of the dispersing disc is controlled to be ≥2000 rpm during the addition of the polyester resin solution.
[0049] Optionally, after the polyester resin solution is completely added, the temperature is reduced to 25°C within 5 min, and the dispersion treatment is continued for 0.9-1.5 h.
[0050] The polyester resin solution is immediately cooled, and in the embodiment, the prepared system is cooled by cooling water, which is beneficial to ensure the stability of the structure.
[0051] In a third aspect, the present application provides an adhesive comprising the solvent-based emulsion according to any one of the preceding embodiments or prepared by the method according to any one of the preceding embodiments. The adhesive comprises the following components in parts by mass: 100-150 parts of the solvent-based emulsion, 5-15 parts of the hollow microspheres, 20-40 parts of the flame-retardant filler, 10-30 parts of the curing agent, and 20-100 parts of the solvent.
[0052] The adhesive provided by the present application is a uniform and stable system, which is easy to apply and has strong adhesion and low dielectric constant.
[0053] In an optional embodiment, the hollow microspheres are selected from at least one of PS hollow microspheres, glass hollow microspheres, and PDMS hollow microspheres; the addition of the hollow microspheres can further reduce the dielectric constant and dielectric loss tangent of the entire adhesive layer, and achieve high-speed and high-frequency applications.
[0054] The flame-retardant filler is selected from at least one of phosphorus-based flame retardants, bromine-based flame retardants, nitrogen-based flame retardants, silicon-based flame retardants, metal hydroxide-based flame retardants, metal oxide-based flame retardants, and metal boride-based flame retardants. The curing agent is an open-type isocyanate curing agent, and is preferably at least one of HDI curing agents and IPDI curing agents. The solvent is selected from at least one of butanone, ethyl acetate, toluene, butyl acetate, propyl acetate, methyl isobutyl ketone, and cyclohexanone.
[0055] In a fourth aspect, the present application provides an application of the adhesive according to any one of the preceding embodiments in the preparation of a flexible flat cable, which comprises the following steps: The adhesive is prepared by mixing the solvent-based emulsion, the hollow microspheres, the flame-retardant filler, the curing agent, and the solvent in proportion; After the adhesive is coated on the base film, the adhesive is dried at a temperature of 80-100°C for 20-40s to prepare an intermediate with a dry film thickness of 40-60μm; The intermediate is laminated with a conductor, and then cured at a temperature of 60-100°C for 1-3 days to prepare a flexible flat cable.
[0056] In an optional embodiment, the base film is selected from at least one of PET films, PI films, PEN films, and PTFE films. And / or, the laminating composite conditions include: temperature is 160-200℃, pressure is 0.5-0.8MPa, speed is 1.0-1.5m / min. And / or, the material of the conductor is selected from at least one of copper, copper-tin alloy and copper-iron alloy.
[0057] In a fifth aspect, the present application provides an application of the adhesive as described in any one of the preceding embodiments in the field of printed circuit board, touch screen, electronic equipment and semiconductor product and packaging.
[0058] The features and properties of the present application are further described in detail below in combination with examples.
[0059] Preparation of modified hydrogenated styrene elastomer S001-1 Preparation of modified hydrogenated styrene elastomer d1 In a high-speed mixer, 100 parts of hydrogenated styrene elastomer (KRATON G1650, styrene content 30%), 20 parts of white oil, 0.1 part of p-di-tert-butyl peroxide isopropylbenzene and 2 parts of grafting monomer (MAH) were mixed uniformly, extruded in a twin-screw extruder, pelletized and dried, the product was dissolved by heating with xylene, then poured into acetone, the supernatant was taken, precipitated by adding methanol and filtered, and dried to obtain a reactive group grafted modified hydrogenated styrene elastomer, i.e. modified hydrogenated styrene elastomer, denoted as d1; the grafting rate of d1 was measured to be 1% (the grafting rate data was determined by infrared spectroscopy).
[0060] The relevant parameters of the twin-screw extruder are: screw diameter 35mm, L / D=0.36, screw speed 150-300rpm, temperature setting: feeding zone 140℃, melt mixing zone 160℃, reaction zone 170℃, homogenization / exhaust zone 170℃, die head 160℃.
[0061] S001-2 Preparation of modified hydrogenated styrene elastomers d2-d7 and a1 Similar to the preparation steps of d1, the only difference is that the grade of hydrogenated styrene elastomer is different, the styrene content is different, the type of grafting monomer is different, and other parameters are the same. The specific material information and the grafting rate of the final product are summarized in Table 1, which are all mass parts.
[0062] Table 1 Material information for preparing modified hydrogenated styrene elastomer
[0063] S002 Preparation of different types of emulsion S002-1 Preparation of solvent type emulsion D1 30 parts of d1 was added into 70 parts of mixed solvent (mass ratio of methyl ketone: butyl acetate = 1:1), and after complete dissolution by heating to 85℃, the cooling rate was controlled at 3℃ / 5min, and the stirring speed was set at 300rpm in the emulsification kettle, and the temperature was cooled to 55℃. The first system was prepared. 50 parts of polyester resin liquid (the solid content of the polyester resin liquid was 60%, including 30 parts of polyester resin AL061M and 20 parts of methyl ketone solvent) was added to the first system, and the addition rate was controlled at 2 parts / min, and the dispersing disc speed was set at 2500rpm.
[0064] After the polyester resin liquid was added, cooling water was immediately used for cooling treatment, and the temperature was reduced to 25℃ within 5min, and the temperature was maintained at 25℃ for 1h of dispersion. The reactive group grafted modified hydrogenated styrene elastomer solvent emulsion, i.e. solvent emulsion, was obtained, which was recorded as D1.
[0065] The solid content of the solvent emulsion D1 was measured to be 40%, and the rotational viscosity was 2034cPs (the rotational viscosity was tested according to GB / T 1632-93, and was tested by using a BROOKFIELD viscosity instrument) ; the prepared D1 was milky white and uniform, and remained uniform after being placed for one week.
[0066] S002-2 Preparation of solvent emulsions D2-D9 and A1-A6 Similar to the preparation steps of D1, the only difference was that the types of modified hydrogenated styrene elastomer, other reagents in the mixed solvent and the polyester resin liquid were different, and other parameters were the same. The specific material information was summarized in Table 2.
[0067] Table 2 Material information for preparing solvent emulsion
[0068] The specific parameters of the polyester resin were as follows: the Tg of AL061M was -6℃, the number average molecular weight was 21442, the hydroxyl value was 4.1 mgKOH / g, and the acid value was 0.3 mg KOH / g; the Tg of AL177 was 15℃, the number average molecular weight was 25414, the hydroxyl value was 4.2 mg KOH / g, and the acid value was 0.9 mg KOH / g. Among them, the acid value was tested according to GB / T 12008.5-2010; the hydroxyl value was tested according to GB / T 12008.3-2009; the number average molecular weight and the molecular weight distribution were tested according to GB / T 36214.1-2018, and were measured by using a GPC instrument; the Tg was tested according to GB / T 19466.2-2004, and was measured by using a DSC instrument.
[0069] S002-3 Preparation of mixed resin liquid A7, all in parts by mass: A7 was prepared by adding 20 parts of D1 and 20 parts of polyester resin AL061M into 60 parts of toluene solution, heating to complete dissolution at 100°C, to obtain a system mixed resin liquid A7 with a solid content of 40% by mass fraction.
[0070] S003 Preparation of adhesive and flexible flat cable Example 1 A adhesive was prepared by grinding and dispersing 100 parts of D1, 30 parts of flame-retardant filler OP935, 5 parts of PS hollow microspheres and 20 parts of solvent butanone in a grinder, and separately storing 10 parts of curing agent E405-80T, wherein the PS hollow microspheres were purchased from Suzhou Zhiyi Microspheres Technology Co., Ltd. KBsphere®0.1PS.
[0071] After the two components of the adhesive were thoroughly mixed, a 200µm coater was used to coat the surface of a PET base film with a thickness of 50µm; After coating, the film was baked at a temperature of 100°C for 40s to obtain a dry film with a thickness of 50µm; A copper wire was placed in the middle of the dry film, and a roll press was used for rolling, with a rolling temperature of 180°C, a speed of 1.2m / min, and a rolling pressure of 0.6Mpa. After rolling, the sample was placed in a 60°C oven for 2 days to obtain a flexible flat cable (FFC) sample.
[0072] Examples 2-12 and Comparative Examples 1-3 Similar to the preparation steps of Example 1, the only difference was that the types of solvent-based emulsions, the amounts of hollow microspheres, the amounts of solvents, and the amounts of curing agents were different. The specific material information and the products prepared in the corresponding examples are summarized in Table 3, all in mass fraction.
[0073] Table 3 Material information for preparing adhesive and flexible flat cable
[0074] Test Example 1 In this test example, the flexible flat cables (FFC) prepared in Examples 1-12 and Comparative Examples 1-3 were tested for the following properties. The data of Examples 1-7 are summarized in Table 4-1, and the data of Examples 8-12 and Comparative Examples 1-3 are summarized in Table 4-2.
[0075] Test items and corresponding test methods are as follows: (1) Test item: covering property Test method: a. The rolled FFC sample (without baking) was quickly cut along one side with a sharp art knife (note to avoid the adhesive tape of the positioning conductor).
[0076] b. Take about 10 mm wide sample, fix the sample on the digital microscope sample base, select 100 times magnification to observe the cross-section conductor covering condition.
[0077] After the above sample preparation and testing, the pass or fail of the covering is determined. If all the wires have no incomplete covering phenomenon, it is qualified and marked as OK, otherwise it is unqualified and marked as NG.
[0078] (2) Test item: copper wire peel force Test method: a. After drying one layer of substrate, cut out a 5cm*5cm window, and then composite with another layer of substrate and conductor.
[0079] b. Test the peel force of the conductor and sample on the universal testing machine, the peel direction is 180°, the stretching rate is 300mm / min, and the peel force value is recorded.
[0080] (3) Test item: high temperature and humidity resistance Test method: refer to GB / T 2423.50-2019 "Environmental testing: constant humidity and heat, mainly for accelerated testing of components".
[0081] Put the FFC sample into the constant temperature and humidity chamber, set the test conditions as (temperature 85℃, humidity 85%RH, time 2000 hours), after the test is completed, take out the sample and cool it to room temperature, observe whether there are bubbles around the wires, whether there are open glue around the wires, one of the two or both are NG, and the peel force of the wires is tested.
[0082] (4) Test item: cold and hot impact Test method: put the FFC sample into the cold and hot impact test chamber, set the test conditions as (-50℃ (0.5h), 150℃ (0.5h)), after 1000 cycles, take out the sample and cool it to room temperature, observe whether there are bubbles around the wires, whether there are overflow glue at the terminals (upper) of the wires, one of the two or both are NG, and the peel force of the wires is tested.
[0083] (5) Test item: high temperature overflow glue Test method: put the FFC sample in an oven at a temperature of 85℃ for 96 hours, observe whether there is obvious overflow glue at the terminals (upper) of the wires, overflow glue >0.3mm is NG, and overflow glue ≤0.3mm is OK.
[0084] (6) Test item: low temperature bending property Test method: refer to ASTM D522-D522M-17-2021.
[0085] The FFC sample was placed in a -40 °C refrigerator for 4 h, and then was taken out and bent at 180° on a folding resistance tester. The number of times of fracture or crack was recorded.
[0086] (7) Test item: dielectric constant and dielectric loss tangent Test method: The dielectric constant and dielectric loss tangent of the adhesive layer were tested according to GB / T 1693-2007 "Method for Determining Dielectric Constant and Dielectric Loss Tangent of Vulcanized Rubber".
[0087] Table 4-1 Performance test results
[0088] Table 4-2 Performance test results
[0089] From the performance results in Tables 4-1 and 4-2, it can be seen that: Comparative Examples 1 and 2, the grafted modified SEBS and polyester resin were prepared into solvent type emulsion, which can form obvious IPN structure in the adhesive layer, thereby greatly improving the flexibility, modulus and dielectric properties of the adhesive layer; From Examples 1-7, it can be seen that grafted modified SEBS, SEPS and SIBS can be prepared into solvent type emulsion, and the application of these emulsions in adhesives has excellent flexibility, modulus and dielectric properties; Comparative Examples 1, 8 and Comparative Example 1, the addition of PS hollow microbeads can significantly reduce the dielectric constant and dielectric loss tangent of the product, but too much PS hollow microbeads will cause the copper wire peeling force to decrease and the cost to increase; Comparative Examples 1, 9 and 10, different amounts of curing agent will affect the overall modulus of the adhesive layer, thereby affecting the copper wire peeling force and low temperature bending property; Comparative Examples 1 and Comparative Example 3, the graft modification rate of maleic anhydride needs to reach a certain level, otherwise it will affect the IPN structure after curing, resulting in a decrease in high temperature overflow performance; Comparative Examples 11 and 12, the solvent system is very important for the preparation of solvent type emulsion. Through the different solubilities of different solvents to different blocks and the induction of soft segment crystallization nucleation in the solvent system during the cooling process, different solvent systems have a great influence on the performance of the emulsion.
[0090] Test Example 2 This test example analyzes the state of solvent type emulsions D1-D9 and A1-A6. The pictures of the solvent type emulsions in different states are shown in Figures 1-3 ; Among them, Figure 1 is a uniform and stable milky white emulsion, Figure 2 is a phase-separated emulsion, Figure 3A solution in a clear and transparent state.
[0091] In summary, the solvent type emulsion provided by the embodiment of the present application is prepared by emulsifying the modified hydrogenated styrene elastomer with a suitable polyester resin, and the solvent type emulsion of O / O type is obtained; by controlling the cross-linking and curing conditions, the phase separation degree of the hydrogenated styrene elastomer and the polyester can be controlled to achieve the cross-linking interpenetrating network structure, and the adhesive prepared has the characteristics of uniform stability, convenient sizing, strong adhesion, good adhesion to the base film and conductor, and simple processing. The adhesive layer formed by the adhesive has the characteristics of lower dielectric constant and dielectric loss tangent, and higher elastic modulus under the condition of maintaining flexibility, so that the final material structure is more stable and has better heat resistance, and is expected to be widely applied. The adhesive used in FFC application can achieve copper wire peeling force ≥ 130 gf / mm, low temperature bending property ≥ 20 times, dielectric constant ≤ 2.30, and dielectric loss tangent ≤ 0.0030.
[0092] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Various modifications and changes can be made by those skilled in the art based on the spirit and principles of the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A solvent-based emulsion, characterized in that, The solid content of solvent-based emulsions is 35%-45%; By weight, it comprises the following components: 20-40 parts modified hydrogenated styrene elastomer, 60-80 parts mixed solvent and 48-55 parts polyester resin liquid.
2. The solvent-based emulsion according to claim 1, characterized in that, The modified hydrogenated styrene elastomer comprises, by weight parts, the following components: 80-100 parts hydrogenated styrene elastomer, 14-22 parts white oil, 0.08-0.12 parts p-tert-butylperoxyisocyanurate, and 1.5-2 parts grafted monomer; the grafting rate of the modified hydrogenated styrene elastomer is 0.8%-1.2%. The hydrogenated styrene elastomer is selected from at least one of SEBS, SIBS, and SEPS; the grafted monomer includes at least one of the following groups: epoxy group, acid anhydride group; Preferably, SEBS and SEPS have the following characteristics: number average molecular weight of 50,000-150,000, styrene content of 30%-40%, and elongation of 500%-800%; SIBS has the following characteristics: number average molecular weight of 80,000-150,000, styrene content of 15%-25%, and elongation of ≥800%. Preferably, the preparation of the modified hydrogenated styrene elastomer includes the following steps: Hydrogenated styrene elastomer, white oil, p-tert-butylperoxyisopropylbenzene and grafted monomer are mixed evenly in proportion, and then extruded, pelletized and dried in a twin-screw extruder at a temperature of 160℃-170℃ to obtain modified hydrogenated styrene elastomer. Preferably, the grafting monomer is selected from at least one of maleic anhydride, glycidyl acrylate, allyl glycidyl ether, glycidyl methacrylate, and itaconic anhydride.
3. The solvent-based emulsion according to claim 1, characterized in that, The mixed solvent comprises butanone in a volume ratio of 1:(0.8-1.3) and other reagents, wherein the other reagents are selected from at least one of butyl acetate, propyl acetate, methyl isobutyl ketone and dimethyl carbonate; And / or, the solvent of the polyester resin liquid includes methyl ethyl ketone (MEK) with a solid content of 58%-65%; Preferably, the polyester resin has a Tg of -30°C to 15°C, a number-average molecular weight of 10,000-40,000, a hydroxyl value of 3 mg KOH / g-10 mg KOH / g, and an acid value of 0 mg KOH / g-5 mg KOH / g. Preferably, the polyester resin is selected from at least one of AL061M and AL177.
4. A method for preparing a solvent-based emulsion as described in any one of claims 1-3, characterized in that, Includes the following steps: The modified hydrogenated styrene elastomer and the mixed solvent were mixed evenly at a temperature of 85℃-95℃, and then cooled to 50℃-60℃ to obtain the first system. Polyester resin liquid was added to the first system to prepare a solvent-based emulsion.
5. The preparation method according to claim 4, characterized in that, The temperature of the reaction system was reduced to 50℃-60℃ at a rate of 2℃ / 5min-3℃ / 5min. And / or, the polyester resin solution is added to the first system at a rate of 1.5 parts / min to 2.5 parts / min; Preferably, after the polyester resin liquid is completely added, the temperature is lowered to 25°C within 5 minutes, and the dispersion treatment is continued for 0.9-1.5 hours.
6. An adhesive, characterized in that, Includes the solvent-based emulsion as described in any one of claims 1-3 or the solvent-based emulsion prepared by the preparation method as described in any one of claims 4-5; By weight, the adhesive comprises the following components: 100-150 parts solvent-based emulsion, 5-15 parts hollow microspheres, 20-40 parts flame-retardant filler, 10-30 parts curing agent and 20-100 parts solvent.
7. The adhesive according to claim 6, characterized in that, The hollow microspheres are selected from at least one of PS hollow microspheres, glass hollow microspheres, and PDMS hollow microspheres; And / or, the flame-retardant filler is selected from at least one of phosphorus-based flame retardants, bromine-based flame retardants, nitrogen-based flame retardants, silicon-based flame retardants, metal hydroxide flame retardants, metal oxide flame retardants, and metal boride flame retardants; And / or, the curing agent is an open-type isocyanate curing agent, preferably at least one of HDI curing agent and IPDI curing agent; And / or, the solvent is selected from at least one of butanone, ethyl acetate, toluene, butyl acetate, propyl acetate, methyl isobutyl ketone, and cyclohexanone.
8. The application of an adhesive as described in any one of claims 6-7 in the preparation of flexible flat cables, characterized in that, The fabrication of flexible flat cables includes the following steps: An adhesive is prepared by mixing solvent-based emulsion, hollow microspheres, flame-retardant filler, curing agent and solvent in a certain proportion; After the adhesive is coated on the base film, it is dried at 80℃-100℃ for 20s-40s to obtain an intermediate with a dry film thickness of 40μm-60μm. The intermediate is laminated with the conductor and then cured at 60℃-100℃ for 1-3 days to obtain a flexible flat cable.
9. An application as described in claim 8, characterized in that, The base film is selected from at least one of PET film, PI film, PEN film and PTFE film; And / or, the conditions for the lamination process include: a temperature of 160℃-200℃, a pressure of 0.5MPa-0.8MPa, and a speed of 1.0m / min-1.5m / min; And / or, the material of the conductor is selected from at least one of copper, copper-tin alloy and copper-iron alloy.
10. The application of an adhesive as described in any one of claims 6-7 in the fields of printed circuit boards, touch screens, electronic devices, semiconductor products, and packaging.
Citation Information
Patent Citations
Thermoplastic resin composition, adhesive film and wiring film using same
CN102382382B
Polyolefin hot melt adhesive, making method thereof and composite insulating material applying polyolefin hot melt adhesive
CN109628015A
Polyester resin compositions, adhesives and laminates
CN110121533B
High flow, hydrogenated styrene-butadiene-styrene block copolymers and applications
TW201339268A